2022
DOI: 10.3390/bios12080581
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cysteamine and Glutaraldehyde Chemicals for Robust Functionalization of Substrates with Protein Biomarkers—An Overview on the Construction of Biosensors with Different Transductions

Abstract: Currently, several biosensors are reported to confirm the absence/presence of an abnormal level of specific human biomarkers in research laboratories. Unfortunately, public marketing and/or pharmacy accessibility are not yet possible for many bodily fluid biomarkers. The questions are numerous, starting from the preparation of the substrates, the wet/dry form of recognizing the (bio)ligands, the exposure time, and the choice of the running buffers. In this context, for the first time, the present overview summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…A standard immobilization protocol to immobilize antibodies to the gold surface of the IDE was adapted for this project [7]. All reagents and proteins used for immobilization and antigen testing are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…A standard immobilization protocol to immobilize antibodies to the gold surface of the IDE was adapted for this project [7]. All reagents and proteins used for immobilization and antigen testing are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In technological applications, CA is chiefly utilized for the functionalization of various conductive surfaces, thus serving as a platform for the further attachment of biorecognition layers that enable the specific detection of desired analytes (reviewed in ref ). Other recent applications include, e.g., the covalent attachment of CA onto graphene oxide in the engineering of a selective and high-performance Hg­(II) adsorbent, the controlled etching and tapering of Au nanorods by CA, the use of CA as a linker for the controlled self-assembly of Au nanorods, or the introduction of Cu-CA nanoparticles as a new type of radiosensitizer …”
Section: Introductionmentioning
confidence: 99%
“…Glutaraldehyde contains aldehyde groups at both ends of the molecule and can bind to the amine groups in cysteamine and gelatin. 31 Of note, certain studies have reported that glutaraldehyde can undergo acetalization with the hydroxyl groups of alginate. 32 However, this cross-linking reaction occurs only under acidic conditions.…”
mentioning
confidence: 99%
“…The bioconjugation process (Figure S4) involves sequential functionalization of the Au surface with cysteamine and glutaraldehyde and subsequent coating with 0.1% gelatin (Bloom 300, Type A). Glutaraldehyde contains aldehyde groups at both ends of the molecule and can bind to the amine groups in cysteamine and gelatin …”
mentioning
confidence: 99%